2009
DOI: 10.1111/j.1748-3743.2009.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

The research/practice nexus: underlying assumptions about the nature of research uptake into practice in literature pertaining to care of the older person

Abstract: Much has been written about the link between practice and research in the nursing and health literature. The literature from fields of practice relating to care of the older person is no exception. Enhancing best practice to effectively meet the needs and desires of older people, and provide an optimal working environment for those providing that care, requires sustainable synergies between research and practice. However, the perception of a gap(s) between 'what we know' and 'what we do' persists in the writin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…In line with studies from Garam et al (2009) and Day et al (2009), participants in this study described how they perceived themselves to be involved in the development of care, and some even indicated that they were producers of research. We suggest that the participants in this study are moving toward a culture of knowledge searching and reflection, which positively informs the everyday thoughts and actions of all carers.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In line with studies from Garam et al (2009) and Day et al (2009), participants in this study described how they perceived themselves to be involved in the development of care, and some even indicated that they were producers of research. We suggest that the participants in this study are moving toward a culture of knowledge searching and reflection, which positively informs the everyday thoughts and actions of all carers.…”
Section: Discussionsupporting
confidence: 61%
“…This enabled all staff units to have equal opportunity to participate in the implementation. As a result, most units were able to pursue the stepwise journey of the PAR model and to take active charge over their situation, thus avoiding falling into a linear, passive mode of implementation that Garam et al (2009) claim does not work. Exceptions to this were the two units whose staff had divergent opinions, and thus repeatedly opposed the agreed improvement areas, resulting in only progressing half way through the process.…”
Section: Methodological Considerationmentioning
confidence: 99%
“…Based on the findings in this review, future researchers are encouraged to focus on issues of external validity as outlined by the RE-AIM framework, including research that: (i) targets diverse populations; (ii) incorporates and tests theories of behavioural change in real world settings; (iii) operationalizes and reports intervention critical content that enables replication and translation; (iv) explores innovative measures for physical activity behaviours and fall risk; and (v) evaluates the feasibility and acceptability of fall prevention interventions. Strong partnerships among researchers, clinicians, and community members will help interventions become more realistic and relevant (Baumbusch et al, 2008; Garnham et al, 2009; Hanson et al, 2006). …”
Section: Resultsmentioning
confidence: 99%
“…those findings and put them into practice (Garnham et al, 2009). Related to this linear concept of the research process is a body of research and thought about barriers and enablers with respect to the uptake and use of research findings in practice (Greenhalgh et al, 2004;Rycroft-Malone, 2006;Scott et al, 2008).…”
Section: Focusmentioning
confidence: 99%